BARRIERS IN CLINIC TO DISCUSSING SEXUAL DYSFUNCTION DUE TO MULTIPLE SCLEROSIS. Issue 11 (14th October 2015) - Tudor, Katarina Ivana; Eames, Stefani; Haslam, Collette; Panicker, Jalesh
Abstract : Background: Sexual dysfunction is underdiagnosed in patients with multiple sclerosis (pwMS). Little is known about barriers faced by patients and health care professionals (HCPs) in discussing sexual problems. Patients and methods: 74 PwMS (20 male, 54 female (mean age 45, 877±8, 823 years)) and 99 HCPs (8 male, 91 female; 82 (83%) nurses) completed questionnaires evaluating barriers to discussing sexual problems in clinic and sexual dysfunction (MSISQ-15 and ASEX), specifically developed for this study. Results: Symptoms that interfere most with sexual activity are: Takes too long to orgasm (69.11%), bladder symptoms (66.17%), less intense orgasm (66.17%), lack of sexual interest (60.29%), genital numbness (50%). Most common barriers cited by patients include the prominence of other MS symptoms (43.5%), presence of family/friends in consultation room (41.8%), not being asked (37.3%). HCPs identified presence of family/friends in consultation room (57.6% agree), faced lack of knowledge (48.4% agree), patient not ready (44.3% agree), lack of time (42.2%). Conclusions: Sexual dysfunction is common in both men and women following multiple sclerosis. However both patients and HCPs face barriers to addressing the problem. Providing time and privacy during the consultation to discuss sexual dysfunction, and training to HCPs will help to address these barriers.